Association Between Foot Care and the Incidence of Diabetic Foot Ulcers in Patients with Diabetes Mellitus - Anissa Suci Aprilya; Dessy Hadrianti; Zaqyyah Huzaifah; Solikin (Fakultas Kedokteran, Universitas Papua, 2025)
Diabetes mellitus (DM) is a chronic disease that can lead to serious complications, one of which is diabetic foot ulcer (DFU). Inadequate foot care increases the risk of ulcer development; therefore, its association needs to be examined scientifically. This study aimed to analyze the association between foot care and the incidence of diabetic foot ulcers in patients with diabetes mellitus. A correlational analytical design with a cross-sectional approach was employed. The sample consisted of 60 patients with diabetes mellitus selected using purposive sampling. Foot care data were collected using the Nottingham Assessment of Functional Footcare (NAFF) questionnaire, while the incidence of diabetic foot ulcers was assessed through an observation checklist. Data were analyzed using Spearman’s rho correlation test. The results demonstrated a statistically significant association between foot care and the incidence of diabetic foot ulcers (p = 0.008 < α = 0.05). Patients with poor foot care tended to experience diabetic foot ulcers with greater severity. In conclusion, appropriate foot care plays an important role in the prevention of diabetic foot ulcers. Therefore, health education and the establishment of routine foot care practices should be strengthened to reduce the risk of complications and improve the quality of life of patients with diabetes mellitus.